2002
DOI: 10.1007/bf02967599
|View full text |Cite
|
Sign up to set email alerts
|

A case of neurilemmoma of the breast

Abstract: Neurilemmoma of the breast is rarely seen, although it is common at intracranial or peripheral sites. There have been only 14 cases described in the literature. We present the fifteenth case of a 64-year-old woman with neurilemmoma of the breast, the first to be diagnosed by fine needle aspiration cytology. Fibroadenoma must be distinguished from this tumor. Complete removal is the treatment of choice, considering the possibility of local recurrence and malignant change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
7
0
4
Order By: Relevance
“…Only 5 and 4 cases have been reported regarding mammographic and ultrasonographic images, respectively. On ultrasonography, three cases revealed a well-demarcated hypoechoic mass with a benign appearance, 11,15,17 while the other case showed a cystic mass with a heterogeneous papillary lesion. 12 Kuo and Changchien reported the ultrasonographic patterns of seven cases of retroperitoneal schwannoma to differ in each case due to cystic degeneration, hemorrhaging, and the varieties of schwannoma tissue itself.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Only 5 and 4 cases have been reported regarding mammographic and ultrasonographic images, respectively. On ultrasonography, three cases revealed a well-demarcated hypoechoic mass with a benign appearance, 11,15,17 while the other case showed a cystic mass with a heterogeneous papillary lesion. 12 Kuo and Changchien reported the ultrasonographic patterns of seven cases of retroperitoneal schwannoma to differ in each case due to cystic degeneration, hemorrhaging, and the varieties of schwannoma tissue itself.…”
Section: Discussionmentioning
confidence: 96%
“…18 The tumor in our case also had a large cystic area, which suggested degenerative change. On mammography, two cases revealed the presence of a well-defined mass, 11,12 two cases showed no mass, 15,17 and one case showed an ill-defined area of dense soft tissue. 13 In the breast the preoperative differential diagnosis of schwannoma, fibroadenoma, carcinoma, and phyllodes tumor may present some difficulties.…”
Section: Discussionmentioning
confidence: 96%
“…Since none of the above findings was present in our patient, there was no family history, and no clear evidence of tumors was observed in the brain or spinal cord system on the diagnostic images, it was possible to rule out von Recklinghausenʼs disease. Schwannoma of the breast was first reported by Collins et al 4) , and as far as we were able to determine in a search of the literature, there have been very few cases of schwannoma developing in the breast region in Japan, with only 10 cases, including our own, ever having been reported in the country 2,[5][6][7][8][9] . Ages have ranged from 18 to 82 years (mean: 54.4 years), and the most common site of origin has been the upper outer quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of a preoperative diagnosis of fibroadenoma based on a combination of diagnostic imaging, etc., being made in many cases. The case reported by Tohnosu et al has been the only case in which it was possible to make a definitive diagnosis of schwannoma preoperatively 5) , and they reported that the diagnostic method was FNA biopsy and that diagnosis was possible because the cells contained a large amount of cytoplasm and exhibited a palisading pattern. Tetsuhara et al 10) describe Antoni A schwannomas as characterized by tumor cells that are spindle-shaped, exhibit little atypia, grow in a fascicular manner, mainly course in an intricate manner, and exhibit a whorled pattern, and by nuclei that exhibit palisading in a horizontal row.…”
Section: Discussionmentioning
confidence: 99%
“…Rares en sont les formes malignes. Depuis la première publication en 1973 par Collins [5] traitant d'une localisation mammaire d'un schwannome bénin, 22 cas ont été publiés et sont résumés dans le Tableau 1 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionunclassified